Coastal Adaptation Planning in Fairbourne, Wales: lessons for Climate Change Adaptation. (14th March 2020) - Buser, Michael
ABSTRACT: Adaptation to climate change is emerging as a central objective and policy frame for coastal communities. This paper examines recent climate change adaptation efforts in the UK, centring on the case of Fairbourne, Wales. The village is facing the long-term prospect of flooding and inundation due to the impacts of sea level rise. The recent Shoreline Management Plan for the area has recommended realignment of the coast and eventual decommissioning of Fairbourne. The paper draws on a qualitative research methodology of interviews, policy review and observation to narrate the case and provide key insights and lessons for planners working in environmentally vulnerable coastal settings and managing climate adaptation processes.